Map showing Newfoundland railway and steamship system - Reid Newfoundland Company (1928)
Colour. Dated June-December 1928. Relief shown by hachures and spot heights. Bar scale in miles. Shows rail and steamship lines. Includes ancillary map: Newfoundland map showing Newfoundland railway & steamship system. Verso includes timetables, tourist information and a location map. Includes illustrations: S.S. Kyle -- S.S. Caribou.